Use of CPG on management of type 2 diabetes among diabetes care teams in North-East Malaysia - A. Rahman, Nor Azlina; Ismail, Aziz Al-Safi; Yaacob, Nor Azwany (Japan International Cultural Exchange Foundation (JICEF), 2008)
Objective: A study was conducted at all health centres in Kelantan in North East Malaysia to describe the sociodemographic factors of the members of diabetes care teams and the use of Clinical Practice Guidelines (CPG) on Management of Type 2 Diabetes Mellitus among them. Design: A cross-sectional study Materials and Methods: A total of 176 members of diabetes care teams participated in this study. Their sociodemographic data, knowledge, attitude and practice (KAP) regarding the management of type 2 diabetes and their use of the related CPG were gathered from a validated questionnaire. Results: The median age of the subjects was 36 years old (IQR = 16) and the median duration of service was eleven years (IQR = 17). Majority of them were females (60.8%) and Malays (95.5%). Their mean percentage of total knowledge score was 78.7% (SD = 11.4%), the median total percentage of attitude score was 82.9% (IQR = 22.9%) and the median percentage of total practice score was 90% (IQR = 13.3%). Majority of them claimed always doing diabetes screening on patients with risk factors (64.0%), always giving diet education (72.4%) and stop smoking advice to patients (83.1%), always doing yearly foot examination (70.8%) and completing patients’ green diabetic card on every visit (81.9%). However, less percentage of subjects claimed always ensuring yearly fundoscopy (40.4%) or referral to ophthalmologist (54.8%), always doing HbA1c test twice yearly (57.1%) or doing ECG on newly diagnosed patients (45.0%). Conclusion: Self-reported use of CPG on Management of Type 2 Diabetes Mellitus among members of diabetes care teams in North East Malaysia is satisfactory.